Hemophagocytic lymphohistiocytosis secondary to refractory acute myeloid leukemia resolved after second line treatment with azacitidine plus venetoclax - Claudio Fozza (Mediterranean Journal of Hematology and Infectious Diseases)
Hemophagocytic lymphohistiocytosis (HLH), also defined as hemophagocytic syndrome (HPS), represents a potentially life-threatening hyperinflammatory syndrome, characterized by impaired function of cytotoxic T lymphocytes, natural killer cells and macrophages. The main clinical features of HLH are prolonged fever, hepatosplenomegaly, cytopenia, hypertriglyceridemia, hyperferritinemia and hemophagocytosis in bone marrow, liver, spleen or lymph nodes. Secondary HLH typically occurs in conjunction with severe infections, malignancies or autoimmune disorders and intensive chemotherapy, potentially complicating treatment of acute myeloid leukemia (AML) in around 10% of cases. Herein we report for the first time a case of HLH secondary to refractory/relapsed AML resolved after a second line treatment with azacitidine plus venetoclax, thus offering a new potential therapeutic perspective in the context of a life-threatening clinical scenario.